Pemberdayaan Potensi Dan Edukasi Masyarakat Di Desa Tamberu Alet, Batumarmar, Pamekasan - Rosita, Eva; Rindiani, Rindiani; Safitri, Yuliana; Safarina, Nur Afni; Hasanah, Wardatul (STAI Publisistik Thawalib Jakarta, 2022)
Community empowerment is a very important service activity and must be carried out in an effort to free the community from various adversity, backwardness and backwardness. One of the villages that is considered necessary for community empowerment activities to be carried out is the village of Tamberu Alet Batustar, Batumarmar, Pamekasan. The community empowerment activities in the village are carried out with an interdisciplinary and cross-sectoral approach, namely through service programs. This service is carried out in two fields, namely economics and education. In the field of student education, it has been carried out successfully by holding an educational program for the mindset of kindergarten parents through teaching, mentoring and in the field of economics making products.